2014
DOI: 10.1002/jca.21364
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a repeated immunoadsorption in patients with dilated cardiomyopathy after recurrence of severe heart failure symptoms

Abstract: In DCM patients, who experience a significant improvement of LVEF and heart failure symptoms after IA/IgG but a subsequent relapse during follow up, repeated IA/IgG may be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…We decided to enroll 40 patients in total assuming radionuclide LVEF was increased by 3.1% according to our preliminary finding . Although previous report defined 5% or more increase in LVEF as a responder , we did not perform responder/nonresponder analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to enroll 40 patients in total assuming radionuclide LVEF was increased by 3.1% according to our preliminary finding . Although previous report defined 5% or more increase in LVEF as a responder , we did not perform responder/nonresponder analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several autoantibodies found in sera from patients with DCM play a role in mediating cardiac damage and provide arrhythmic substrates , resulting in sudden cardiac death . Immunoapheresis removing these autoantibodies has been developed to treat DCM patients with refractory heart failure . In these preliminary trials except for Müller, et al , intravenous immunoglobulin was replaced after each session of apheresis, because the columns used in these trials nonspecifically removed immunoglobulin.…”
Section: Introductionmentioning
confidence: 99%
“…The immunoadsorption is designed to remove antibodies directed to beta-adrenergic receptors which are believed to have a pathogenic role in the disease. Reinthaler (16**) compared immunoadsorption columns for both total immunoglobulin and for selective removal of the IgG3 subclass. Some patients showed surprisingly long-term benefits of this treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of ejection fraction was shown in 10, improved functional class in 7, and reduced natriuretic peptides in 5 (Table 3). 3,37,38,[43][44][45][46][47][48][49][50][51] Reinthaler et al 52 suggested that initial responders to therapy, who subsequently had a recurrence of autoantibodies, seemed to benefit from repeat immunoadsorption. All of these studies were small and with one exception were not randomized or blinded.…”
Section: Proof Of Concept Immunoadsorptionmentioning
confidence: 99%